Expecting the Unexpected : Tools and Policy Considerations to Support the Recovery and Resilience of the Tourism Sector - World Bank (Washington, DC, 2022)
Tourism has been, and continues to be, one of the most affected sectors by the pandemic, resulting in negative socio-economic consequences for host communities in destinations as well as for underlying endowments that rely on tourists’ expenditure for maintenance and management. The aim of this report is to provide insights regarding the types of interventions governments have already implemented and policy considerations for supporting the recovery and resilience of the tourism sector going forward, particularly in light of structural demand and supply-side transformations precipitated or accelerated by Coronavirus disease 2019 (COVID-19). The report studies the challenges for recovery faced by governments and the sector from the context of preexisting market and government failures that have been exacerbated by the crisis, as well as those emerging from the pandemic. The report includes several key findings and recommendations.